Science projects about light - Gardner, Robert, 1929-; Delisle, Stephen F. (Berkeley Heights, N.J. : Enslow, 1994)
Presents experiments dealing with light using simple materials that may be found around school or home. Offers activities that are appropriate for science fairs.
"Updated with internet sites"--Cover.
Includes bibliographical references (p. 120) and index.
Book Report.
School Library Journal.
Wilson's Junior High School.
4-6
Keywords: Light -- Experiments -- Juvenile literature; Science projects -- Juvenile literature; Science -- Exhibitions -- Juvenile literature; Experiments; Light -- Experiments; Science projects; Light -- Experiments; Science projects; Science -- Experiments